Analysis of the Influence of ChatGPT on Students Learning Motivation in Improving English Intensive Reading Skill - Ramadhan, Siti; Aeni, Nur; Fauzan, Muhammad Miftah (Journal of Excellence in English Language Education, 2026)
This qualitative study aims to explore how ChatGPT influences students’ learning motivation in the context of English language learning. The study is motivated by the increasing integration of artificial intelligence in education, which is believed to enhance students’ engagement and self-directed learning. Data were collected through semi-structured interviews with ten sixth-semester students of the English Education Department at Universitas Negeri Makassar, who were selected using purposive sampling. Thematic analysis was applied to identify recurring patterns in students’ perceptions. The findings indicate that ChatGPT has a positive impact on students’ learning motivation through three main aspects: autonomy, competence, and engagement. ChatGPT enhances students’ sense of autonomy by providing flexible access to information, quick responses, and personalized assistance that allow learners to control their own learning pace. It strengthens students’ competence by simplifying difficult materials, offering detailed explanations, and building their confidence in understanding English reading texts. Furthermore, ChatGPT promotes engagement by creating interactive learning experiences and providing enjoyable, low-pressure communication that reduces anxiety and increases participation. Several participants also mentioned that ChatGPT encourages curiosity and inspires them to explore learning materials beyond classroom instruction. However, some students reported a potential drawback, noting that overreliance on ChatGPT may decrease self-initiative in independent study. Overall, the results suggest that ChatGPT functions as an effective virtual learning assistant that supports both intrinsic and extrinsic motivation, fosters self-regulated learning, and contributes to students’ enthusiasm for developing English proficiency.